2015
DOI: 10.1186/s40001-014-0078-0
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic resonance imaging and endorectal ultrasound for diagnosis of rectal lesions

Abstract: Endorectal ultrasonography (ERUS) and magnetic resonance imaging (MRI) allow exploring the morphology of the rectum in detail. Use of such data, especially assessment of the rectal wall, is an important tool for ascertaining the perianal fistula localization as well as stage of the cancer and planning it appropriate treatment, as stage T3 tumors are usually treated with neoadjuvant therapy, whereas T2 tumors are initially managed surgically. The only advantage of ERUS over MRI is the possibility of assessing T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
45
0
3

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(48 citation statements)
references
References 72 publications
0
45
0
3
Order By: Relevance
“…Endorectal ultrasound is believed to be more sensitive in identifying early tumors, but it is highly operator dependent and large studies show that staging accuracy is not as high as previously reported (18,19). The only advantage of ERUS over MRI is the possibility of assessing T1 tumors that could be managed by transanal endoscopic microsurgery (20).…”
Section: Discussionmentioning
confidence: 96%
“…Endorectal ultrasound is believed to be more sensitive in identifying early tumors, but it is highly operator dependent and large studies show that staging accuracy is not as high as previously reported (18,19). The only advantage of ERUS over MRI is the possibility of assessing T1 tumors that could be managed by transanal endoscopic microsurgery (20).…”
Section: Discussionmentioning
confidence: 96%
“…Ultrasonography is highly accurate enabling the visualisation of rectal wall abnormalities and the identification of lesions localised beyond the rectum [7]. ERUS has also an important role in the assessment of anorectal fistulae, determining type, level, branching and internal opening and recurrences of fistulae [8].…”
Section: Discussionmentioning
confidence: 99%
“…The sphincter anal complex is formed by the muscles that represent the continuation of circular layer of the muscularis propria of the rectum, the striated external anal sphincter, and puborectal muscles, which belong to the levator ani muscles [4]. The lowest point of the external anal sphincter represents the upper anal margin; it is called the anal verge and is the principal landmark for rectal measurements [4]. The pectinate (dentate) line is located 1.5-2 cm upwards from the anus and separates the canal anal into the anatomical part located below the line and the surgical part located above the line [4].…”
Section: Anatomy Of the Anorectal Regionmentioning
confidence: 99%
“…The lowest point of the external anal sphincter represents the upper anal margin; it is called the anal verge and is the principal landmark for rectal measurements [4]. The pectinate (dentate) line is located 1.5-2 cm upwards from the anus and separates the canal anal into the anatomical part located below the line and the surgical part located above the line [4]. The surgical anal canal extends from the pectinate line to the level of the puborectalis sling, which corresponds to the anorectal junction.…”
Section: Anatomy Of the Anorectal Regionmentioning
confidence: 99%